Globalization, economic freedom and human rights - Dreher, Axel; Gassebner, Martin; Siemers, Lars-H.R. (Munich, 2010)
"Using the KOF Index of Globalization and two indices of economic freedom, we empirically analyze whether globalization and economic liberalization affect governments’ respect for human rights using a panel of 106 countries over the 1981-2004 period. According to our results, physical integrity rights significantly and robustly increase with globalization and economic freedom, while empowerment rights are not robustly affected. Due to the lack of consensus about the appropriate level of empowerment rights as compared to the outright rejection of any violation of physical integrity rights, the global community is presumably less effective in promoting empowerment rights. "